2024
DOI: 10.1038/s41598-024-55854-4
|View full text |Cite
|
Sign up to set email alerts
|

Research on the coupling mechanism and influencing factors of digital economy and green technology innovation in Chinese urban agglomerations

Xuesi Zhong,
Ziyi Duan,
Chang Liu
et al.

Abstract: This paper examines the coupling coordination degree between digital economy and green technology innovation in 19 urban agglomerations across China from 2011 to 2020. Through the analysis of the coupling coordination degree model, spatial autocorrelation, multi-distance spatial clustering analysis, kernel density analysis and grey correlation model, this study uncovers the mechanism of coupling between digital economy and green technology in Chinese urban agglomerations. Data analysis revealed a significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Geographical economics research has demonstrated that regional development disparities could evolve into issues of unbalanced regional development or lead to phenomena such as the "siphon effect" and the "radiating effect" in regional development [6][7][8]. Efficacious cross-regional collaborative frameworks have the potential to magnify the radiating effects from more developed to less developed regions, significantly enhancing the digital allocation of financial resources and spurring innovative outputs, thus advancing the cause of common prosperity [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Geographical economics research has demonstrated that regional development disparities could evolve into issues of unbalanced regional development or lead to phenomena such as the "siphon effect" and the "radiating effect" in regional development [6][7][8]. Efficacious cross-regional collaborative frameworks have the potential to magnify the radiating effects from more developed to less developed regions, significantly enhancing the digital allocation of financial resources and spurring innovative outputs, thus advancing the cause of common prosperity [9,10].…”
Section: Introductionmentioning
confidence: 99%